Evaluation of Tax Service Application User Satisfaction for Sustainable Service Digitization - Ramadhan, Hanifa Maulani; Agusti, Rosalita Rachma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
E-TPT is an android-based application that is used in carrying out public services, especially in the field of taxation. The main service of this application is the online queue menu, but in its implementation the use of this application is still experiencing some problems so that follow-up is needed in overcoming the problem. The purpose of this study was to determine and explain the effect of perceived ease and usefulness on user satisfaction and behavioral interest in using the E-TPT Application. Therefore, research is carried out using quantitative methods and involves a number of theories to evaluate the use of applications, the theoretical models used include Theory Acceptance Model (TAM), Theory Reaction Action (TRA), accompanied by model development which includesPerceived usefulness, Perceived ease of use,Behavioral Intention to Use, and User Satisfaction. Perceived usefulness has a significant effect on user satisfaction, perceived usefulness has a significant but not significant effect on behavioral interest in using applications, and perceived usefulness has a significant effect on behavioral interest in using applications through user satisfaction. Furthermore, perceived ease of use has an insignificant but not significant effect on user satisfaction, perceived ease of use has a significant effect on behavioral interest in using applications, and perceived ease of use has an insignificant effect on behavioral interest in using applications through user satisfaction. User satisfaction has a significant effect on behavioral interest in using the application. Increasing user satisfaction and interest in using this application can be done by developing applications. In the application development process, you can consider the speed of the application in completing work, improve user performance and user convenience in application control as well as conduct research and planning related to the needs of taxpayers on the application.